Hodgkin’s lymphoma with lymphocyte depletion and diffuse bone marrow infiltration - Carballo, Fernando (2011)
We present the case of a 38 year-old male, farmer, born in Lamas, San Martin (Peruvian jungle), who for the past 8 months suffered of diarrhea, intermittent fever, abdominal pain, weight loss and severe anemia. On admission the patient was lucid and exhibited malaise, pallor and generalized lymphadenopathy (size less than 0.5 cm) hepatosplenomegaly and abdominal displaceable dullness. Abdominal computed tomography showed hepatosplenomegaly and retroperitoneal, mesenteric and other adenopathies. Node biopsy revealed Reed-Sternberg cells, mononuclear cells, eosinophiles and scarce lymphocytes. Immunohistochemical node staining was positive for CD15 and CD30 antibodies. Bone biopsy showed diffuse fibrosis, mononuclear cells and scarcity of lymphocytes. In situ hybridization for EBV Epstein Barr virus was positive in neoplastic cells.